2021
DOI: 10.1111/jdv.17522
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the number of early melanomas diagnosed during the COVID‐19 pandemic: a single‐centre cohort study

Abstract: The expression pattern of interferon-inducible proteins reflects the characteristic histological distribution of infiltrating immune cells in different cutaneous lupus erythematosus subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 6 publications
3
22
0
12
Order By: Relevance
“…A significant decrease was observed in the number of diagnoses performed monthly (Fig 1 ) during the first few months of lockdown, which is similar to the finding reported in the studies published by Gisondi et al 2 and Javor et al 3 in Italy. An even higher reduction in the number of diagnoses performed monthly was observed in the studies by Koch et al 4 and Lallas et al, 5 in which the decrease in melanoma diagnosis was 31.2% and 36.4%, respectively.…”
mentioning
confidence: 75%
“…A significant decrease was observed in the number of diagnoses performed monthly (Fig 1 ) during the first few months of lockdown, which is similar to the finding reported in the studies published by Gisondi et al 2 and Javor et al 3 in Italy. An even higher reduction in the number of diagnoses performed monthly was observed in the studies by Koch et al 4 and Lallas et al, 5 in which the decrease in melanoma diagnosis was 31.2% and 36.4%, respectively.…”
mentioning
confidence: 75%
“…Reductions of new melanoma and/or cSCC diagnoses have also been observed in Spain 5 and Chile 6 . A large Canadian study showed a reduction of most cases of cancer during the COVID‐19 pandemic especially for melanoma and cervical, endocrinological and prostate cancers 7 .…”
Section: Figurementioning
confidence: 91%
“…Reductions of new melanoma and/or cSCC diagnoses have also been observed in Spain 5 and Chile. 6 A large Canadian study showed a reduction of most cases of cancer during the COVID‐19 pandemic especially for melanoma and cervical, endocrinological and prostate cancers. 7 Contrasting results have been observed in two studies conducted in England, 8 , 9 while in Belgium 10 no particular variations in skin cancer diagnosis have been observed during the COVID‐19 pandemic.…”
mentioning
confidence: 99%
“…Decreased numbers of new malignant melanoma (MM) cases, [1][2][3][4] increased tumour thickness and occurrence of metastases of newly diagnosed melanomas 5,6 in the time of the first SARS-CoV-2 wave compared to the same months in 2019 have been recently reported in some European countries and the USA. However, Sweden reported stable numbers of new detected melanomas with no significant effect of pandemic on tumour stages, 7 possibly due to the absence of the lockdown.…”
Section: Dear Editormentioning
confidence: 98%